A biomimetic generative optimization design for conductive heat transfer based on element-free Galerkin method. (January 2019) - Lin, Qiyin; Wang, Jihong; Hong, Jun; Liu, Zheng; Wang, Zhihua
Abstract: A generative method inspired by leaf venation is presented for the layout design of heat conduction channels. This method, which is based on the simulation of the growth process of leaf venation, also employs the element-free Galerkin (EFG) method to discretize the design domain for the heat conduction structures. Using the EFG method, the growth of each cooling branch follows any arbitrary direction. In addition, a divergence criterion for the cooling branches is presented. The potential effectiveness and efficiency of this generative optimization design approach is investigated through a numerical examination of the "volume-to-point" heat conduction problem.